2008
DOI: 10.1007/s10164-008-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Egg rejection behaviour in the great reed warbler (Acrocephalus arundinaceus): the effect of egg type

Abstract: Egg discrimination in hosts of the common cuckoo Cuculus canorus is frequently studied by experimental parasitism, using model cuckoo eggs. We compared egg rejection behaviour of the great reed warbler Acrocephalus arundinaceus to either model cuckoo eggs made of plastic or painted real host eggs. We simultaneously parasitised host nests by two different egg types to simulate cuckoo parasitism. A previous study revealed very similar, ca. 70%, rejection rates against both of these egg types (beige or bluish bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…As revealed by experiments with model eggs, some hosts of the Common Cuckoo, e.g., the Great Reed Warbler which is relatively large in terms of body mass and bill-size and is readily able to use grasp ejection of cuckoo eggs, always first try to puncture eggs (Lotem et al, 1995;Antonov et al, 2006a; for similar results see also Honza and Moskat, 2008). Comparisons with the evidence from several similar studies on other Sylviidae suggest that puncture ejection is the ancestral mode of rejection in this family Procházka and Honza, 2003;Honza et al, 2004).…”
Section: Parasite Eggshell Strength and The Evolution Of Rejection Modessupporting
confidence: 49%
“…As revealed by experiments with model eggs, some hosts of the Common Cuckoo, e.g., the Great Reed Warbler which is relatively large in terms of body mass and bill-size and is readily able to use grasp ejection of cuckoo eggs, always first try to puncture eggs (Lotem et al, 1995;Antonov et al, 2006a; for similar results see also Honza and Moskat, 2008). Comparisons with the evidence from several similar studies on other Sylviidae suggest that puncture ejection is the ancestral mode of rejection in this family Procházka and Honza, 2003;Honza et al, 2004).…”
Section: Parasite Eggshell Strength and The Evolution Of Rejection Modessupporting
confidence: 49%
“…Larger objects were mostly buried only in pre-incubation, whereas smaller objects were mostly ejected during pre-incubation and incubation (Guigueno and Sealy 2009). In a related study, Honza and Moskát (2008) found that the type of material (plastic or painted host eggs) influenced whether hosts punctured the object (painted host egg) or pecked the object over and over to create a hole in the hard material (plastic egg); however, both object types were rejected at similar frequencies.…”
Section: Responses To Object Typesmentioning
confidence: 93%
“…For treatments, we manipulated one or more of the hosts' own eggs in a nest, painting dark brown spots (see below) onto the eggshell. We used painted C. Moskát and others real eggs, following Honza and Moskát (Honza and Moskát, 2008). The eggs of great reed warblers are suitable for such types of painting experiments because a great reed warbler egg is as large as a cuckoo egg (Török et al, 2004).…”
Section: Materials and Methods Study Site And Speciesmentioning
confidence: 99%
“…This period of monitoring was justified by our previous studies on this host species, where latency of rejection was 1-5days for each type of parasitic egg: for real cuckoo eggs in natural parasitism (Moskát and Hauber, 2007), and plastic model cuckoo eggs and painted great reed warbler eggs in experimental parasitism (e.g. Honza and Moskát, 2008).…”
Section: Controlmentioning
confidence: 99%